The Role of Extracurricular English Club Activities to Improve Students’ Speaking Skills at MTsN 1 Jeneponto - Aeni, Zahratul; Korompot, Chairil Anwar; Fauzan, Muhammad Miftah (Journal of Excellence in English Language Education, 2026)
This study aims to analyze the role of English Club extracurricular activities in improving students' speaking skills at MTsN 1 Jeneponto. Speaking skills are very important for students to communicate effectively in English, but many students face difficulties in mastering this skill due to limited opportunities to practice in a regular classroom environment. The method used is qualitative with an observational research design of 7 samples involved in English club extracurricular activities, using a purposive sampling technique. The researcher used observation, interview, and documentation methods as research instruments to obtain results.